Reading Japan cool : patterns of manga literacy and discourse - Ingulsrud, John E. (Lexington Books, 2009)
Japanese animation, video games, and manga have attracted fans around the world. The characters, the stories, and the sensibilities that come out of these cultural products are together called Japan Cool. This is not a sudden fad, but is rooted in manga--Japanese comics--which since the mid-1940s have developed in an exponential way. In spite of a gradual decline in readership, manga still commands over a third of the publishing output. The volume of manga works that is being produced and has been throughhistory is enormous. There are manga publications that attract readers of all ages and gen.